From bench to beside to cure spinal cord injury: lost in translation? - Hug, Andreas; Weidner, Norbert (International review of neurobiology, 2012)
Despite intense efforts to overcome the inhospitable milieu for axonal regeneration within the damaged spinal cord an evidence-based repair strategy promoting relevant functional improvement is still not available for spinal cord injured individuals. Nevertheless, several preclinical axonal regenerative strategies were developed all the way to phase I/II clinical trials, which have recently been terminated. The aim of this chapter is to critically review translated preclinical treatment strategies with respect to their conformity with previously published guidelines and requirements for preclinical studies leading to clinical trials in human subjects with spinal cord injury (SCI). Cell-based strategies (macrophage and embryonic stem cell grafting) and the administration of C3 transferase inhibitors and anti-Nogo-A antibodies were investigated. Overall, these four approaches comply with preclinical quality standards to varying degree. For future preclinical analyses, several additive components such as defined criteria for robustness of observed effects, a clear confirmation of underlying structural mechanisms, and the implementation of appropriate preclinical rehab approaches should be considered in order to increase the quality and consequently the likelihood of respective therapeutic strategies to succeed in human individuals suffering from SCI.
Gesehen am 12.11.2018